2014
DOI: 10.1007/s11434-013-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of polybrominated diphenyl ethers in the surface sediment of the East China Sea

Abstract: The concentrations of polybrominated diphenyl ethers (PBDEs) were determined in the surface sediments of 20 locations in the East China Sea (ECS). The P PBDEs (sum of 13 PBDE congeners, without brominated diphenyl ether 209 (BDE209) ranged from 2.6 to 49 pg g -1 (dry weight) with an average of 21 pg g -1 , which fell at the low end of the global range. The spatial distribution presented an offshore decreasing trend towards the outer shelf and along the coastline, suggesting a direct influence of the inputs by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
3
1
Order By: Relevance
“…PCDD/F and PCB concentrations were generally comparable to the previous results in the lower reaches areas of Yangtze River (Nie et al, 2013;Shen et al, 2006;Sun et al, 2005;Yang et al, 2009). Unlikely, PBDE concentration in Yangtze River Delta S12 was much higher than the observation by Chen et al (2006) in the intertidal zone of the Yangtze River Delta and Li et al (2014) in the estuary and East China Sea. This could be attributed to the different sampling sites and reported congeners.…”
Section: Yangtze River Basinsupporting
confidence: 84%
See 2 more Smart Citations
“…PCDD/F and PCB concentrations were generally comparable to the previous results in the lower reaches areas of Yangtze River (Nie et al, 2013;Shen et al, 2006;Sun et al, 2005;Yang et al, 2009). Unlikely, PBDE concentration in Yangtze River Delta S12 was much higher than the observation by Chen et al (2006) in the intertidal zone of the Yangtze River Delta and Li et al (2014) in the estuary and East China Sea. This could be attributed to the different sampling sites and reported congeners.…”
Section: Yangtze River Basinsupporting
confidence: 84%
“…This could be attributed to the different sampling sites and reported congeners. Li et al (2014) reported the determination of 13 BDE congeners without BDE-209, while extremely high level of BDE-209 was observed in the composite sample in our study (99.9% of 14 PBDEs).…”
Section: Yangtze River Basincontrasting
confidence: 46%
See 1 more Smart Citation
“…Several researchers also found a positive correlation between the distribution of PBDEs and organic carbon in sediment of a river estuary [4, 43]. However, poor correlations have also been observed between TOC and PBDEs in other areas [2, 41, 62, 66, 67]. …”
Section: Controlling Factorsmentioning
confidence: 98%
“…It is still hold true for the study in East China Sea. It presented a broad similar pattern between low-percentage sandy sediments and the concentrations of PBDEs [62], while the rule is not suitable for the South China Sea [41]. …”
Section: Controlling Factorsmentioning
confidence: 99%